PERANCANGAN PROYEK LOW RISE APARTMENT/FLAT DENGAN PENDALAMAN GREEN DESIGN OLEH KONSULTAN E STUDIO - Gunawan, Evan Junior; Wardhani, Dyah Kusuma (Aksen : Journal of Design and Creative Industry, 2022)
Population growth that continues to increase in the midst of limited land is a paradoxical essential problem in facing the development of the world of modern architectural and interior design today. This condition will lead to a negative impact on the environment, thus making the existence of these three problems very crucial to be responded to in an architectural and interior design strategy that is concerned about the environment. E Studio as an architectural and interior consulting company that focuses on implementing the principles of building design that is functional, environmentally friendly (green design), and has character (ambiance) is the answer in its active contribution to responding to these existing problems, i.e., limited land, environmental damage, and the density of the population that is indicated to occur in the current modern era. The method used for design exploration uses the concept of programmatic form processing with a green design approach to answering the problems and needs of the design users. Bringing up one theme, PARADOX, to realize that the presence of a building can essentially make it non-contradictory to the surrounding natural environment. The application of green design is applied to the processing of building mass generation, optimization of natural lighting and ventilation, concern about user health and comfort, and materials selection that can be recycled to reduce project waste in the future. Keywords: Architecture, E Studio, Green Design, Interior, Low Rise Apartment